The contribution of principal leadership style, teachers’ professional competence and school climate on the quality of learning outcomes at Vocational High School in Padang - Sari, Putri Purnomo; Ganefri, Ganefri; Anwar, Muhammad (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Learning outcomes are the results achieved in the form of numbers or scores after being given a test of learning outcomes at the end of each meeting. The quality of learning outcomes itself is influenced by several factors; the principal's leadership style, professional competence and school climate. This research aims to know the contribution of (1) principal’s leadership style, (2) professional competence, and (3) school climate on the quality of learning outcomes at Vocational High School (SMK) in Padang. This research used a quantitative method. The data were collected by using questionnaire. The data were analyzed by using multiple linear regressions using LISREL. The results showed that there was a positive and significant relationship between the principal leadership style and the teachers’ professional competence on the quality of learning outcomes at several vocational schools in Padang. There was a positive and significant relationship between the principal leadership style and professional competence through the school climate on the quality of learning outcomes at several vocational schools in Padang.